Ultra-precision single-point diamond turning of a complex sinusoidal mesh surface using machining accuracy active control - Ning, Peixing (Strojniški vestnik, 2021)
Single-point diamond turning (SPDT) assisted with slow tool servo (STS) is the most commonly utilized technique in the fabrication of optical modules. However, the tool path significantly affects the quality of the machined surface. In order to realize the determined machining accuracy effectively, a tool path generation (TPG) method based on machining accuracy active control (MAAC) is presented. The relationship between tool path and machining error is studied. Corner radius compensation (CRC) and the calculation of chord error and residual error are detailed. Finally, the effectiveness of the proposed approach is verified through a machining error simulation and a cutting experiment of a complex sinusoidal mesh surface fabrication.
Keywords: aktivni nadzor točnosti obdelave; complex sinusoidal mesh surface; kompleksna sinusoidna površina; machining accuracy active control; machining error prediction; napovedovanje napake obdelave; single-point diamond turning; točkovno struženje z diamantnim orodjem